Formation of a two-dimensional oxide via oxidation of a layered material. Issue 22 (27th May 2022) - Camilli, Luca; Capista, Daniele; Tomellini, Massimo; Sun, Jianbo; Zeller, Patrick; Amati, Matteo; Gregoratti, Luca; Lozzi, Luca; Passacantando, Maurizio
Abstract : Oxidation mechanism and kinetics of the layered model system GeAs. Abstract : We investigate the oxidation mechanism of the layered model system GeAs. In situ X-ray photoelectron spectroscopy experiments performed by irradiating an individual flake with synchrotron radiation in the presence of oxygen show that while As leaves the GeAs surface upon oxidation, a Ge-rich ultrathin oxide film is being formed in the topmost layer of the flake. We develop a theoretical model that supports the layer-by-layer oxidation of GeAs, with a logarithmic kinetics. Finally, assuming that the activation energy for the oxidation process changes linearly with coverage, we estimate that the activation energy for As oxidation is almost twice that for Ge at room temperature.